Decreased expression of microRNA-17 in hippocampal tissues and blood from mice with depression up-regulates the expression of PAI-1 mRNA and protein - Lv,Min (2020)
This study determined the expression of plasminogen activator inhibitor-1 (PAI-1) and microRNA (miR)-17 in a mouse depression model. Forty male mice were divided evenly into control and depression groups. A chronic unpredictable mild stress (CUMS) model was constructed. qRT-PCR was used to determine the expression of PAI-1 mRNA and miR-17. Western blotting and ELISA were used to determine expression of PAI-1 protein. Dual luciferase reporter assay was carried out to identify direct interaction between miR-17 and PAI-1 mRNA. The mice with depression had elevated PAI-1 mRNA and protein in hippocampal tissues and blood. Expression of miR-17 was decreased in hippocampal tissues and blood from mice with depression. miR-17 bound with the 3′-UTR of PAI-1 mRNA to regulate its expression. This study demonstrated that miR-17 expression in hippocampal tissues and blood from mice with depression was decreased while expression of PAI-1 mRNA and protein was up-regulated. miR-17 participated in depression in mice by regulating PAI-1.